Montenegro : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses the first phase, to be constructed from 2015 to mid-2019, comprises a 41-kilometer section that is to provide an efficient and safe transport link between Podgorica and the poorest northern region in Montenegro. It runs through the mountainous terrain in the center of the country that is economically undeveloped. Due to its large cost (25 percent of 2017 GDP), the first phase of the highway has used up most of Montenegro's fiscal space and will crowd out other productive spending. For the foreseeable future, the second and third parts of the highway could only be financed with concessional funds, because loans would destabilize the debt sustainability of Montenegro. The government's main motivation for this large project is the need to improve connectivity, particularly to Europe through Serbia, boost tourism and trade, improve road safety, and strengthen national security. The highway is a part of Montenegro's plans to integrate the Montenegrin transport network with those of neighboring countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet